(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of knowledge of epilepsy care of primary caregivers at Thanh Hoa Provincial Mental Hospital in 2025. Methods: Cross-sectional descriptive study with non-probability convenience sampling method, pre-designed instrument set. Results: The main caregivers are mostly the patient’s parents (76%), 64.8% of caregivers have a correct understanding of the disease concept and 67.2% know the cause of the disease. 75.2% of caregivers have correct knowledge of how to use medicine for the patient, and over 80% choose the correct treatment measures when an epileptic seizure occurs. 96% of caregivers have correct knowledge in preventing complications for the patient and 88.8% have correct knowledge in nutritional care. Conclusion: Primary caregivers’ knowledge of epilepsy care was relatively good, with 16.8% having good knowledge, 62.4% having fair knowledge, and 20.8% having poor knowledge.